Enhancing the densification of ceria ceramic at low temperature via the cold sintering assisted two-step sintering process - Charoonsuk, Thitirat; Sukkha, Usa; Kolodiazhnyi, Taras; Vittayakorn, Naratip (My University, 2018)
The cold sintering process (CSP) in the transient aqueous environment of malonic acid is applied in this study to enhance the densification behavior of ceria ceramics at a significantly reduced sintering temperature. Dense ceria ceramics (> 98% relative density) could be achieved after CSP at 180 °C, followed by the sintering at 1100 °C/4 h. As expected, the CSP can improve the compaction of the particles before sintering, resulting in ceria ceramics with a fine microstructure of submicrometer scale of grain sizes. All samples show the single phase of cubic fluorite structure with no significant change of lattice parameter. Finally, electrical conductivity of CSP and conventionally sintered ceramics is investigated. This communication emphasizes the advantage of the CSP to reduce the sintering temperature without deterioration of the structure and properties of the final ceramics.
Keywords: Ceria; Cold sintering; Densification; Malonic acid